On nerve complications of exanthematic typhus - Odriozola, Ernesto (1919)
In this inaugural lecture, I intend to make the study of a patient, which for us is of greater importance, in that it is a disease that reigns in our mountains as endemic. assume periodic exacerbations presenting characters epidemics, often violent and deadly. Sick of that I will deal has had an attack of typhus. The year 1856, when yellow fever swept our coast, was also developed extensive typhus epidemic in our mountains, which caused heavy casualties. Some professionals, including the British Medical ARCHIBALDO SCMITH, argued that this trans-epidemic, was none other than the yellow fever that had suddenly appeared on our coast. For this reason, we undertook a lively discussion to unravel the nature of the epidemic, being subsequently shown that yellow fever was not only typhus. Unfortunately this error has been perpetuated and many authors of scientific notoriety executed, entered it, as Professor Manson, for example. Everything about this interesting issue will be the subject of a well-documented study that will appear soon in the "Annals of the Faculty of Medicine", due to the untiring efforts of my friend Dr. JULIAN ARCE.